Digital consumer transformation to enhance Dawah in Muhammadiyah special branch Taiwan - Sari, Norma; Sunardi, Sunardi; Winiarti, Sri; Ahdiani, Ulaya (Universitas Ahmad Dahlan, 2024)
Muhammadiyah has grown rapidly throughout the world in quantity through special branches as well as quality by targeting the Dawah model, including digital Dawah. Muhammadiyah realizes that the development of digital dawah requires quality human resources and continues to develop to increase its capacity to promote dawah using digital technology. The leadership of the Muhammadiyah Special Branch Taiwan is one of the overseas branches that has developed digital dawah since its establishment. The purposes of the service are to help Muhammadiyah Special Branch Taiwan enhancing the dawah by applying digital technology and to help to transform digital consumers into digital creator. We expect this service will strengthen Muhammadiyah Special Branch Taiwan networking. This program contributes to the Muhammadiyah Special Branch in Taiwan to manage membership and activities, to link with other Islamic Organizations, and to spread the dawah internationally through an informatics system developed by the UAD team.